Answer:
a = 1.5
b = 1.75
Step-by-step explanation:
First, we need to solve and replace the result in the initial equation as:
Then, this equality apply only if the coefficient of is equal in both sides and the constant is equal in both sides.
It means that we have two equations:
So, using the first equation and solving for a, we get:
Finally, replacing the value of a in the second equation and solving for b, we get:
Hello:
(poq)(x) = p(q(x))= p(x-3) = 2(x-3)²-4(x-3) = 2(x²-6x+9)-4(x-3)
(poq)(x) = 2x²-12x+18-4x+12
(poq)(x) = 2x²-16x+30... (answer : C )
Hello! What type of work is that so I can specifically know! :)
Oh okie so cute ☺️ cute lol
X times 2x=50
2x^2=50
Divide by 2
X^2= 25
X=5
Length is 10 ft